2017
DOI: 10.4172/2155-9562.1000453
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fish oil Vs. Resolvin D1, E1, Methyl Esters of Resolvins D1 or D2 on Diabetic Peripheral Neuropathy

Abstract: ObjectiveFish oil is enriched in omega-3 polyunsaturated fatty acids primarily eicosapentaenoic and docosahexaenoic fatty acids. Metabolites of these two polyunsaturated fatty acids include the E and D series resolvins. Omega-3 polyunsaturated fatty acids and resolvins have been reported to have anti-inflammatory and neuroprotective properties. The objective of this study was to evaluate the efficacy of menhaden oil, a fish oil derived from the menhaden, resolvins D1 and E1 and the methyl esters of resolvins D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 59 publications
1
22
0
Order By: Relevance
“…ω‐3 PUFAs suppress inflammatory responses by inhibiting the arachidonate cascade in neutrophils, and the stimulation of the G protein‐coupled receptor 120 by DHA exerts anti‐inflammatory effects in macrophages. Recent studies report the anti‐oxidant effects of 4‐hydroxy‐2‐hexanal (4‐HHE), resolvin E1 and protectin D1, which are intracellular metabolites of ω‐3 PUFAs. We also examined the effects of 4‐HHE on the mRNA levels of anti‐oxidant enzymes and found that 4‐HHE increased the mRNA levels of Ho‐1 , Nqo‐1 and Cat (data not shown).…”
Section: Discussionmentioning
confidence: 97%
“…ω‐3 PUFAs suppress inflammatory responses by inhibiting the arachidonate cascade in neutrophils, and the stimulation of the G protein‐coupled receptor 120 by DHA exerts anti‐inflammatory effects in macrophages. Recent studies report the anti‐oxidant effects of 4‐hydroxy‐2‐hexanal (4‐HHE), resolvin E1 and protectin D1, which are intracellular metabolites of ω‐3 PUFAs. We also examined the effects of 4‐HHE on the mRNA levels of anti‐oxidant enzymes and found that 4‐HHE increased the mRNA levels of Ho‐1 , Nqo‐1 and Cat (data not shown).…”
Section: Discussionmentioning
confidence: 97%
“…34,35,38,51 Furthermore, our studies have demonstrated that E and D series resolvins (resolutionphase interaction products), metabolites of eicosapentaenoic and docosahexaenoic acids, respectively, which are known to have anti-inflammatory and neuro-protective properties, may be the active mediators responsible for the effect of fish oil on peripheral neuropathy and nerve regeneration. [51][52][53] Zhang et al performed a systematic review and meta-analysis titled omega-3 polyunsaturated fatty acid oral supplements for improving peripheral nerve health. 54 Most of the randomized trials cited in this review focused on chemotherapy-induced peripheral neuropathy and the authors concluded that there was little support of a therapeutic benefit for omega-3 fatty acid oral supplementation in this patient cohort.…”
Section: Discussionmentioning
confidence: 99%
“…66 In our studies, we have shown that resolvin D1 increases neurite growth by primary cultures of dorsal ganglion neurons and improves corneal nerve density and neural function of diabetic mice. [51][52][53]…”
Section: Discussionmentioning
confidence: 99%
“…To answer this question, it will be important to determine the combined levels of resolvins E1 and D1 as well as neuroprotectin D1 under the conditions used in this study. Previous studies have shown that treating diabetic mice with exogenous resolvin E1 or D1 improves peripheral neuropathy [ 5 7 ]. It has also been shown that resolvin D1 and neuroprotectin D1 can stimulate neurite outgrowth by dorsal root ganglion or trigeminal ganglion neurons in culture [ 6 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…We have also shown that cotreatment of type 1 diabetic mice with menhaden (fish) oil and salsalate is more effective toward neuropathy than menhaden oil alone and that circulating resolvin D1 levels are increased when salsalate is combined with menhaden oil [ 5 ]. Lastly, we have demonstrated that treating either type 1 or type 2 diabetic mice with daily injections of resolvin E1 or D1, metabolites of eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), respectively, most abundant omega-3 polyunsaturated fatty acids found in fish oil, improves peripheral neuropathy [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%